Applying a Risk-benefit Analysis to Outcomes in Tuberculosis Clinical Trials - Miyahara, Sachiko (Clin Infect Dis, 2020)
Although it is common to analyze efficacy and safety separately in clinical trials, this could yield a misleading study conclusion if an increase in efficacy is accompanied by a decrease in safety. A risk-benefit analysis is a systematic approach to examine safety and efficacy jointly. Both the “rank-based” and “partial-credit” methods described in this paper allow researchers to create a single, composite outcome incorporating efficacy, safety, and other factors. The first approach compares the distribution of rankings between arms. In the second approach, a score can be assigned to each outcome category, considering its severity and comparing the mean or median scores of arms. The methods were applied to the A5279/Brief Rifapentine-Isoniazid Efficacy for TB Prevention study, and design considerations for future clinical trials are discussed, including the challenge of arriving at a consensus on rankings/scorings. If well designed, a risk-benefit analysis may allow for a superiority comparison and, therefore, avoid setting a noninferiority margin. Clinical Trials Registration. NCT01404312 (A5279).